Effects of typhoons on primary production and dissolved oxygen in the East China Sea - Yang, Wen; Wu, Haokun; Zhang, Wenxia (Frontiers in Marine Science, 2024)
Previous investigations confirm that typhoons deliver both dissolved oxygen and nutrient sources via promoting vertical/lateral exchanges between water masses. The former one replenishes oxygen for the bottom water and prevents persistent oxygen depletion, while the latter one facilitates primary production and subsequent subsurface oxygen consumption. However, it is left unknown if typhoons ultimately result in net gain or loss of dissolved oxygen during the passage. Tropical cyclone information, satellite observations, and numerical simulations were used to investigate the response of primary production and dissolved oxygen dynamics to typhoons. Results imply that both typhoon intensity, and distance between typhoon track and the Changjiang estuary control the magnitude of responses in primary production, air-sea oxygen flux, advection-induced oxygen variation, and oxygen consumption variation. The modelbased oxygen budget analysis indicated that oxygen content increased after the passage of all typhoons occurred between 2011-2020. The findings in this study suggest that typhoons ultimately result in net gain of oxygen. The increased strength and frequency of typhoon in the warming future would play an important role in counteracting deoxygenation, which is likely to slow down the pace of deterioration of the seasonal hypoxia in this region.